Produção de serapilheira em área reflorestada - Moreira, Paulo Roberto [UNESP]; Silva, Osvaldo Aulino Da [UNESP] (Sociedade de Investigações Florestais, 2004)
Litter deposition was measured in a 7,455 m² area reforested with tree species over a redyellow Argisoil of medium texture during one year. This area is owned by Sítio Laranja Azeda,in the subdivision of Pinhal, in Limeira, SP, located in the peripheral depression of the state (22º33'17 S and 47º24'17 W), at an altitude of 567 m. The local climate is classified by Köppen as Cwa-type, with humid and hot summers and dry and cold winters. Litter average production was estimated monthly by 21 0.25 m² collectors, randomly distributed in each of the different topographic situations. Average litter production of undergrowth in the dry season was 697 kg/ha and 407 kg/ha in the wet season. These are intermediate values between the semi-decidual seasonal forest fragments of São Paulo state and the Floresta da Tijuca (reforested area), areas at more advanced stages of secondary succession; and upper values when compared with other reforested areas in São Paulo. The results allowed to conclude that: a) litter production had a strong seasonal variation, especially a more intense deposition during the dryest months; b) litter productions differ in each topographic situation; c) the undergrowth production is a strong sign of the growth and ecological equilibrium of this new forest.

Durante um ano a deposição de serapilheira, em uma área de 7.455 m² reflorestada com espécies arbóreas sobre um Argissolo Vermelho-Amarelo de textura média, foi quantificada. A área deste estudo pertence à propriedade rural denominada sítio Laranja Azeda, no bairro do Pinhal, município de Limeira-SP, localizada na depressão periférica do Estado (22º 33' 17 S e 47º 24' 17 W), a uma altitude de 567 m. O clima local é do tipo Cwa, de acordo com a classificação climática de Köppen, com verão quente e úmido e inverno seco e frio. A produção de serapilheira foi estimada mensalmente por meio de 21 coletores de 0,25 m², distribuídos aleatoriamente por toda área de estudo, colocados em cada uma das situações topográficas verificadas. A produção média de serapilheira na estação seca foi de 697 kg/ha e 407 kg/ha na estação úmida. Estes valores são intermediários quando comparados com os dos fragmentos de floresta estacional semidecidual do Estado de São Paulo e com os da Floresta da Tijuca (área reflorestada), que são áreas em estádios mais avançados de sucessão secundária, e superiores, quando comparados com os de outras áreas reflorestadas de São Paulo. Os resultados obtidos permitem concluir que: a) a produção de serapilheira teve uma forte variação sazonal, tendo ocorrido maior deposição nos meses mais secos; b) há distinção entre produção de serapilheira nas três situações topográficas verificadas; e c) a produção de serapilheira é um forte indicativo do grau de crescimento e equilíbrio ecológico da nova floresta.
Litter production in a reforested
Keywords: Litter production; reforested area; semidecidual seasonal forest; Produção de serapilheira; área reflorestada; floresta estacional semidecidual